(untitled) (New Collegium, 2020)
This work is devoted to the analysis of the outstanding domestic scientist and teacher N. I. Kostomarov contribution to the disclosure of the origins of the history of Ancient Russia and the initial stages of the formation of the ethno-national consciousness of its population. The scientific approaches of the scientist to the analysis of the emergence of statehood in the Old Kiev territory theories are considered. The scientific methods that scientists used to analyze this problem are shown, in particular, the analysis of the primary sources, the linguistic approach to the origin of geographical names and others were used. Particular attention is focused on fine-tuning by domestic scientists the lack of Normans influence on the public people’s life. The article emphasizes that the scientists’ proof of the fallacy of the origin of Russia Norman theory contributed to the development of student interest in Slavic self-knowledge. The understanding of the contribution of N. I. Kostomarov to the question of dividing the Russian population by type of ethnic community and social organization is of considerable academic interest. It is emphasized that among the inhabitants of Kievan Rus, the scientist singled out the ancestors of modern Ukrainian and Russian, whose historical process and folk characteristics continued to receive a more expressive specificity over time. The conclusion is made about the existence and development of its own Slavic state beginning in the process of the formation of Kievan Rus. The practical importance is the identification of creating a nation in Old Kiev times factors in the work of N.I. Kostomarov. The formation of a territorial community, the unity of the country’s population, the power structures of the then society, the development of popular democracy forms, the influence of local self-government on the formation of political unity is of significant. It is noted that the practical importance of studying the national experience combines both with the solution of modern problems of the country and the upbringing of the young generation political development.